2003
DOI: 10.1016/s0886-3350(02)01649-8
|View full text |Cite
|
Sign up to set email alerts
|

Same-day versus first-day review of intraocular pressure after uneventful phacoemulsification

Abstract: The results indicate that moderate IOP spikes (<40 mm Hg) can be left untreated if they are not associated with corneal edema or patient discomfort as they decline spontaneously. Before they are discharged, patients with compromised optic discs or predisposed to retinal or optic nerve pathology should be carefully evaluated the day after surgery to treat IOP elevations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0
6

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 15 publications
2
28
0
6
Order By: Relevance
“…Unlike T, the K maintains the anterior chamber during the surgical procedure through viscoelastic material. However, previous research studies into the use of K during cataract surgeries have found that retained viscoelastic material in patients can result in postoperative IOP spikes [9,10]. The Goniotome (Neomedix, Tustin, CA, USA) is a new device that combines elements of both K and T. Like K, G consists of dual blades that cut into the TM tissue but they are serrated to initiate a double cut more reliably.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike T, the K maintains the anterior chamber during the surgical procedure through viscoelastic material. However, previous research studies into the use of K during cataract surgeries have found that retained viscoelastic material in patients can result in postoperative IOP spikes [9,10]. The Goniotome (Neomedix, Tustin, CA, USA) is a new device that combines elements of both K and T. Like K, G consists of dual blades that cut into the TM tissue but they are serrated to initiate a double cut more reliably.…”
Section: Introductionmentioning
confidence: 99%
“…12,15,16 Cerrahi sonrası GİB artışı her ne kadar kısa süreli gibi görünse de retina sinir lifi rezervi azalmış ileri evre glokomlu hastalarda ciddi sinir lifi kaybına neden olabilir. 17 Ayrıca psödoeksfoliasyon ve pigment dispersiyonu gibi nedenlerle trabeküler dışa akımı azalmış hastalarda ya da daha yüksek koheziviteye sahip VEM'in kullanıldığı hastalarda GİB yüksekliği daha uzun sürebilir. 16,18,19 Bu risk faktör-lerine sahip hastaların cerrahi sonrası yakın takibi önerilmekle birlikte cerrahi sonrası kısa süreli GİB artışının uzun dönem görme alanı kaybına neden olmadığı birçok çalışmada gösterilmiştir.…”
Section: Discussionunclassified
“…16,18,19 Bu risk faktör-lerine sahip hastaların cerrahi sonrası yakın takibi önerilmekle birlikte cerrahi sonrası kısa süreli GİB artışının uzun dönem görme alanı kaybına neden olmadığı birçok çalışmada gösterilmiştir. 17,20 Komplikasyonsuz fakoemülsifikasyon sonrası endotel hücre kaybı kataraktın sertlik derecesi, kullanılan VEM'in ve fakoemülsifikasyon cihazı-nın özellikleri, cerrahın tecrübesi gibi birçok faktöre bağlı olarak %3-30 arasında değişmektedir. 21,22 Bu oranlar çalışmaların tama yakınında kornea merkezinden yapılan endotel hücre sayımlarına dayanmaktadır.…”
Section: Discussionunclassified
“…4 It has been shown that transient spikes in IOP have no effect on the visual field in normal patients. 22,23 However, in patients with a compromised disc, even transient elevations in IOP have been suggested to have a negative impact on patients with pre-existing severe defects. 11,20,[22][23][24][25][26][27][28][29] Yasutani et al 30 have even demonstrated that, without additional therapy, glaucomatous eyes have an elevated IOP on the first postoperative day, which can worsen until the third day before gradually decreasing.…”
Section: Discussionmentioning
confidence: 99%
“…Together with the increased susceptibility of glaucoma eyes to a transiently elevated IOP, 11,20,22,[24][25][26][27][28][29]36,38 it would appear risky to omit this 1-day postoperative check in such eyes, regardless of the prophylactic regime used.…”
Section: Discussionmentioning
confidence: 99%